Rivaroxaban and early periprostethic joint infection: our experience - Di Benedetto, Paolo; Zangari, Andrea; De Franceschi, Dania; Di Benedetto, Enrico Daniele; Cainero, Vanni; Beltrame, Alessandro; Gisonni, Renato; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Periprostethic joint infection (PJI) is a severe post-operative complication after Primary Total Hip Arthroplasty (THA). According to the classification of PJI early acute PJI occurs within 4 weeks from surgery. Some authors think that Rivaroxaban is a risk factor in the incidence of early acute PJI. We analyze our experience about this item. Materials and methods: We analyze our experience from 1st January 2015 to 31th December 2016. We consider all consecutive hip arthroplasty implants in this period. Results: In the 205 patients analysed we not find early acute PJI in Rivaroxaban group nor in the others assuming another kind of thromboprophylaxis. Conclusions: In our series there is no evidence of association between Rivaroxaban and early acute PJI. This is a retrospective cohort study, so we need more studies and more robust experimental designs to confirm these results.